Stress among child protective service workers: Self-reported health consequences. (July 2018) - Griffiths, Austin; Royse, David; Walker, Robert
Abstract: High levels of stress have been associated with several physical and mental health problems including coronary heart disease, acute myocardial infarctions, poor survival from cardiac events as well as changes in the immune and nervous systems. Among stressful professions, social work, with its focus on difficult to serve populations and modest compensation, has received only limited research attention. There is a substantial gap in the literature on how job-related stress among child welfare workers is related to their health and health habits. This study uses self-reported data from a sample of public child welfare workers ( n = 511) to explore the impact of job-related stress and its perceived effect on their health and well-being. Qualitatively, participants mentioned 586 unhealthy habits or behaviors that they attributed to the stress of their positions (e.g. unhealthy eating, substance use, disturbed sleep, lack of exercise, irritability, self-neglect, other troubling behaviors). Additionally, these child welfare professionals described mental health ( n = 214 mentions), physical health ( n = 160 mentions), and work-life imbalance issues ( n = 68 mentions) that they associated to the stress of their positions. Using the qualitative mentions of unhealthy habits by person, a ratio level variable was used to test for mean differences. Findings revealed significant differences in the quantity of unhealthy habits and length of employment at the agency, intention to stay, and self-perception of health. This study makes a first step toward understanding the relationship of job stress and health among child protective service workers. Study findings have potential implications for the high rate of turnover in this field. Policy-makers may need to consider workers' stress and ability to practice self-care as they examine ways to improve retention and protective service outcomes. Highlights: Job stress effects the health and well-being of child welfare professionals. Child welfare professionals mentioned the development of unhealthy habits and behaviors as a consequence of this stress. Significant differences were found in the quantity of unhealthy habits and length of employment, intention to stay, and self-perception of health.